2001
DOI: 10.1016/s1388-9842(01)00138-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced endothelin‐1‐induced contractions in mesenteric arteries from rats with congestive heart failure: role of ETB receptors

Abstract: Ž. Studies of congestive heart failure CHF in man and in experimental CHF have demonstrated elevated circulating levels of Ž . endothelin ET . In order to examine whether there are concomitant ET receptor alterations, the vasomotor effects of Ž . Ž . endothelin-1 ET-1 and sarafotoxin 6c S6c were examined in endothelium-intact and -denuded isolated mesenteric arteries from rats with CHF. CHF was induced by ligation of the left anterior descending coronary artery. Vasomotor responses were Ž . studied using small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Nonetheless, the dilatory role of ET B receptors is not significant in isolated human coronary arterial rings (Pierre & Davenport, 1998). Further data even suggest that in pathology, stimulation of endothelial ET B receptors might be ET-1 Pharmacology detrimental by inducing effects such as cell adhesion or contraction (Bergdahl et al, 2001;Schneider et al, 2007;Sen et al, 2009). This suggests that in pathology the vasodilating effect of endothelial ET B receptor stimulation may be lost.…”
Section: The Endothelium-dependent Responses To Et-1mentioning
confidence: 98%
“…Nonetheless, the dilatory role of ET B receptors is not significant in isolated human coronary arterial rings (Pierre & Davenport, 1998). Further data even suggest that in pathology, stimulation of endothelial ET B receptors might be ET-1 Pharmacology detrimental by inducing effects such as cell adhesion or contraction (Bergdahl et al, 2001;Schneider et al, 2007;Sen et al, 2009). This suggests that in pathology the vasodilating effect of endothelial ET B receptor stimulation may be lost.…”
Section: The Endothelium-dependent Responses To Et-1mentioning
confidence: 98%
“…There is general agreement that in HF, low cardiac output (11,12,16,17) and increased synthesis of vasoconstrictor agents (13,16,17) may contribute to peripheral hemodynamic abnormalities (18). Experimental evidence (19,20) suggests that altered perfusion can stimulate the release of prooxidant superoxide from vascular tissues, impair vasodilatation, and enhance production of peroxynitrite with consequent vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that the vascular ET B and ET A receptors are involved in the atherosclerotic process [2]. Upregulation of the ET-1 and ET B receptor is found in human atherosclerotic lesions [3,4,5] and experimental models of heart failure [6,7]. Increased ET B receptor-mediated responses have been demonstrated in human atherosclerotic arteries [3,4].…”
Section: Introductionmentioning
confidence: 99%